ANALISIS VIDEO PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PENYELESAIAN MASALAH BILANGAN PECAHAN SISWA SD - Ayi Gina Rahmawati; Karlimah Karlimah (IKIP Siliwangi, 2021)
Lack of problem solving ability elementary school students in learning mathematics with fractions. The application of solving mathematical problems of fractions has not been carried out optimally. The provision of mathematics learning media is still very minimal, especially in problem solving, so that it becomes an obstacle to increasing problem solving abilities. Learning media is now not only visual media, there are many kinds of media that can be accessed, such as audio-visual media. Video is one of the audio-visual media that can help the learning process. Now it has been widely circulated on various social media, YouTube channels and learning applications making it easier for students primary schools can access learning. However, not all learning videos are in accordance with the learning objectives, many mathematics learning videos have not achieved the basic competence of mathematics, namely solving mathematical problems. Students' difficulties in solving fractional number problems. The study aims to analyze the feasibility of mathematics learning videos in improving the problem solving abilities of elementary school students. This research approach uses descriptive qualitative. Data collection techniques are through literature studies and documentation studies. Data analysis uses data reduction, data presentation and conclusion drawing. The result of this research is a video feasibility analysis of students' fractional number completion.